Класифікаційні схеми документів - Комова, Марія (Видавництво Львівської політехніки, 2019)
An analysis of the concepts of classification of documents in the context of studying the views of scientists on the nature of the document as a social and communication phenomenon, on the classification features and types of documents.
Keywords: документ; класифікація документів; класифікаційна схема документів